2023
DOI: 10.1002/aenm.202203833
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Perovskite Oxide Development for Thermochemical Energy Storage by a High‐Throughput Combinatorial Approach

Abstract: are highly desirable. [2] The intermittent nature of renewable electricity generated from wind and solar requires considerable compensation from other energy sources, limiting their shares in the power grid. [3][4][5][6] Therefore, energy storage systems, which reduce the temporal and spatial imbalances between electricity generation and consumption, will play a critical role in accelerating the renewable transition. [7] Various energy storage approaches have been proposed to store different forms of energy, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 88 publications
0
0
0
Order By: Relevance
“…Overall, SBF628 would exhibit the lowest average Δ G . In our previous study, we reported a negative correlation between redox oxygen capacity and Δ G of the perovskite oxides . In the current study, a smaller Δ G of SBF628 aligns with its higher overall oxygen capacity.…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…Overall, SBF628 would exhibit the lowest average Δ G . In our previous study, we reported a negative correlation between redox oxygen capacity and Δ G of the perovskite oxides . In the current study, a smaller Δ G of SBF628 aligns with its higher overall oxygen capacity.…”
Section: Resultssupporting
confidence: 76%
“…Despite these limitations, the van't Hoff approach provides a good overall estimation of the reaction enthalpies of the materials. This was supported by the close agreement between the obtained ΔH values for the base material of SrFeO 3−δ in our previous study 27 and those reported in the literature using other methods. 33,45 33 we can see that Ba lowers ΔH, which can translate to a lower energy requirement for CLAS.…”
Section: ■ Introductionsupporting
confidence: 90%
See 3 more Smart Citations